HALAL COSMETIC PURCHASE INTENTION: IN THE PERSPECTIVE OF MUSLIM AND NON-MUSLIM CONSUMER - Zurina Mohaidin,; Nurafni Rubiyanti, (Journal of Islamic, Social, Economics and Development, 2022)
This study intends to explore factors influencing halal cosmetic purchase intention.This research aims to examine the relationship between brand quality and brand trust towardspurchase intention and include religion as a moderator variable to find out the difference inperceptions between Muslim and non-Muslim consumers. An on-line cross-sectional surveywas used to obtain data concerning the purchase of respondents’ cosmetic favorite brands. Thetarget population for this paper encompassed women both Muslims and Non-Muslims. Thesample was taken in Bandung city collaborating 400 respondents (200 respondents areMuslims and the rest are non-Muslims). The data analysis method used is SEM-PLS approachbased on the SmartPLS version of 3.2.7. The hypotheses testing revealed that brand quality andbrand trust influence purchase intention towards halal cosmetic both for Muslim and Non-Muslim consumers. This research also shows that there is the matter between Muslim and Non-Muslim regarding purchase intention influenced by brand quality. Non-Muslim will buy halalcosmetic if they consider the brand are good quality, however both of them (Muslim and Non-Muslim) would buy the brand of halal cosmetic they are trusted.